The metal nanoparticle-induced inflammatory response is regulated by SIRT1 through NF-κB deacetylation in aseptic loosening - Deng, Zhantao (Int J Nanomedicine, 2017)
Aseptic loosening is the most common cause of total hip arthroplasty (THA) failure, and osteolysis induced by wear particles plays a major role in aseptic loosening. Various pathways in multiple cell types contribute to the pathogenesis of osteolysis, but the role of Sirtuin 1 (SIRT1), which can regulate inflammatory responses through its deacetylation, has never been investigated. We hypothesized that the downregulation of SIRT1 in macrophages induced by metal nanoparticles was one of the reasons for osteolysis in THA failure. In this study, the expression of SIRT1 was examined in macrophages stimulated with metal nanoparticles from materials used in prosthetics and in specimens from patients suffering from aseptic loosening. To address whether SIRT1 downregulation triggers these inflammatory responses, the effects of the SIRT1 activator resveratrol on the expression of inflammatory cytokines in metal nanoparticle-stimulated macrophages were tested. The results demonstrated that SIRT1 expression was significantly downregulated in metal nanoparticle-stimulated macrophages and clinical specimens of prosthesis loosening. Pharmacological activation of SIRT1 dramatically reduced the particle-induced expression of inflammatory cytokines in vitro and osteolysis in vivo. Furthermore, SIRT1 regulated particle-induced inflammatory responses through nuclear factor kappa B (NF-κB) acetylation. Thus, the results of this study suggest that SIRT1 plays a key role in metal nanoparticle-induced inflammatory responses and that targeting the SIRT1 pathway may lead to novel therapeutic approaches for the treatment of aseptic prosthesis loosening.